Pengembangan Media Pembelajaran Googlesites Pada Materi Pendapatan Nasional di Kelas XI IPS SMAN 1 Jawilan - Hany Tutut Handayani; Aan Hendrawan; Rudi Hariyadi (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
To build and create enthusiasm for student learning so that students can actively participate in learning activities, it is necessary to develop student-centered learning media. Learning activities really need innovation in learning development because this method can create attraction in learning activities. So with the development of interactive learning media that makes students interested so that it has an impact on increasing student learning motivation, several interactive learning designs are needed to support interesting and fun learning activities. This article introduces Googlesites-based learning media that can directly interact with students. The method used in this research is research and development using the ADDIE development model developed by Dick and Carry. This media was validated by media experts, material experts, and two economics teachers. The suitability of Google Sites media was assessed with an average score of 4.0 which is included in the feasible category.